Communicative-pragmatic and structural-semantic characteristics of performative act of apologizing (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Lingvopragmatic  and structural-semantic characteristics of performative act of apologizing and its functional synonyms is the aim of the article. The conditions of effectiveness are proposed, typical and non-typical performative representations are analyzed, the establishers’ role of such structures are given in the article.
Keywords: performativ; the speech act; apologizing; typical and non-typical performative apologizing